2015
DOI: 10.1364/boe.6.001553
|View full text |Cite
|
Sign up to set email alerts
|

Intravital fluorescence imaging of mouse brain using implantable semiconductor devices and epi-illumination of biological tissue

Abstract: The application of the fluorescence imaging method to living animals, together with the use of genetically engineered animals and synthesized photo-responsive compounds, is a powerful method for investigating brain functions. Here, we report a fluorescence imaging method for the brain surface and deep brain tissue that uses compact and mass-producible semiconductor imaging devices based on complementary metal-oxide semiconductor (CMOS) technology. An image sensor chip was designed to be inserted into brain tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…FRET based fluorescent probes demonstrate large stokes shift due to intramolecular energy transfer, and thus, were selected for use in the on-chip fluorescence detection system with dye-based absorption filter in the present study. 23 Cellular response to extracellular agents was induced by delivering EGF. As presented in Fig.…”
Section: On-chip Fluorescence Imaging and Detection Of Cellular Activitymentioning
confidence: 99%
“…FRET based fluorescent probes demonstrate large stokes shift due to intramolecular energy transfer, and thus, were selected for use in the on-chip fluorescence detection system with dye-based absorption filter in the present study. 23 Cellular response to extracellular agents was induced by delivering EGF. As presented in Fig.…”
Section: On-chip Fluorescence Imaging and Detection Of Cellular Activitymentioning
confidence: 99%
“…(4,7,9) Previous research has already shown that the fabrication of small yet high-resolution image sensors is possible for various purposes, such as observing the brain activity of rodents, (15) illuminating and detecting light in deep biological tissues for optical therapy and diagnosis, (16) and optogenetics. (17) Moreover, it is possible to insert a small image sensor in an incubator to observe cultured cells for a long period of time, (3,6,8,11,12) and also possible to develop a similar image sensor for long-term Förster resonance energy transfer (FRET) observation in a small animal.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several authors have developed neural devices with CMOS image sensors for fluorescence imaging or intrinsic signal imaging. 12,13 Kobayashi et al 9 reported an implantable device with a CMOS image sensor and dual light emitting diodes (LEDs) for photostimulation and fluorescence imaging. The authors reported the use of blue LEDs for photostimulation, green LEDs for fluorescence excitation, and an absorption filter (long-pass liquid photoresist filter: >600 nm) superimposed on the CMOS image sensor, to pass the fluorescence and intercept the stimulation and excitation light.…”
Section: Introductionmentioning
confidence: 99%